ULTRASONOGRAPHIC ASSESSMENT OF FETAL DEATH IN A PET RABBIT - P. Selvaraj; D. Sumathi; Mohammed Ali; M.Venkatesan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A six-month-old pregnant female grey rabbit was presented to the outpatient unit of Madras Veterinary College, with a history of discharge from the vagina, dullness, inappetence and owner was not aware of the mating details. Physical examination revealed a distended abdomen, pain on palpation, skin turgor for more than 2 seconds, with a dull woebegone appearance. On abdominal palpation, there was a hard mass suggestive of pregnancy. There were moderate purulent secretions from the vagina. The temperature was within normal range. The ultrasonographic assessment revealed pregnancy with visualization of fetal bones. However, none of the fetus had heartbeat and no clear visualization of fetal organs. However, fetal bones like skull and ribs were visualized. Ultrasonographic assessment revealed a bi-parietal diameter of 11.43 mm in a few fetus and which was tentatively diagnosed at approximately 19-20 days of pregnancy. Emergency surgery was performed, a hysterectomy was done and fetal contents were collected in sterile swabs were sent for microbial testing.